Perlindungan Konsumen Dalam Transaksi E-Ticketing Pending Payment dan Keterlambatan Konfirmasi E-Ticket Konser Day6 - Yulia Salsa Billa, Ainun; Budi Setianigrum, Reni (PT. Meja Ilmiah Publikasi, 2025)
This study aims to examine the legal protections available to consumers in e-ticketing transactions, particularly in instances of issues such as delayed payments and confirmation of electronic tickets. The focus is on the case of the DAY6 3rd World Tour